Test on the effectiveness of the utilization of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) as an anti-aging cream - Theedens, Maria Theodora; Widodo, Gunawan Pamudji; Astuti, Santi Dwi (Journal of Health Management and Pharmacy Exploration, 2024)
Binahong leaves (Anredera cordifolia (Ten.) Steenis) contain flavonoids, essential oils, saponins, alkaloids and steroids/terpenoids. Antioxidant compounds derived from flavonoid function as protection for the skin from direct exposure to sunlight. This research was conducted to determine the stability and physical quality characteristics of the binahong leaf extract cream preparation and the effectiveness of binahong leaf extract as an anti-aging agent. Binahong leaf powder was extracted using the maceration method using 96% ethanol solvent. Formulations of binahong leaf ethanol extract is based on a concentration ratio of 3% (F1), 5% (F2) and 10% (F3). The resulting cream is of the vanishing cream (O/A) type. The irritation test was carried out on the back of a rabbit test animal which had first been shaved. Testing the effectiveness of anti-aging cream on the skin was experimental, by inducing UV-A light using light from the Exoterra® daylight basking spot and followed by skin analysis of anti-aging parameters (moisture, skin elasticity and percentage (%) of collagen) using the Skin tool Analyzer EH-900U. Analysis used the paired t-Test, one way ANOVA and Tukey test methods to examine the comparative effectiveness of treatments F1, F2 and F3 as anti-aging creams. The results of the research show that the average stability and physical quality of all anti-aging cream preparations of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) have good results and fall within the established standard requirements. The concentration of binahong leaf extract which has the greatest influence on anti-aging effectiveness of F3 (10%), has the best effect compared to other formulas which is characterized by an increase in the parameters of moisture is 19,05%, elasticity is 27,17% and percent (%) collagen is 20,77%.